PENGARUH DIAMETER BATANG DAN STIMULAN ORGANIK TERHADAP PRODUKTIVITAS GETAH KARET (Hevea brisilliensis Muell. Arg) DI PT INDOCO SENDANG TULUNGAGUNG - Suci Nur Fauziah; Galit Gatut Prakosa; Sukadaryati; Febri Arif Cahyo Wibowo (Jurnal Penelitian Hasil Hutan, 2022)
Rubber (Hevea brasiliense Muell. Agr) is a highly traded commodity various industries. Indonesia is the second-largest rubberproducing country in Southeast Asia after Thailand, with most of the land owned by the people where farmers haven’t used renewabletechnology. This study conducted trials of wood vinegar stimulant and organic ethrel stimulant on various diameter classes to knowthe effect of latex productivity. The research was conducted for two months in July-August 2021 at PT Indoco Sendang Tulungagungplot Y, Picisan Village, Boso Hamlet. The variable observed was the weight of the rubber latex in each treatment. There are twotreatment factors, factor A stimulant consist of 4 levels: no treatment (A1), ethrel stimulant (A2), 100% wood vinegar stimulant(A3), 50% wood vinegar stimulant (A4). Factor B stem diameter consists of 3 levels: 10-15 (B1), 16-20 (B2), 21-25 (B3).The method used is a Randomized Block Design (RAK), Honest Significant Difference Test (BNJ) α 5%. There are threereplications with 36 samples. The concentration that has an influence on the weight of the sap is 100% wood vinegar stimulant.